Multifunctional near infrared-emitting long-persistence luminescent nanoprobes for drug delivery and targeted tumor imaging. (January 2015) - Shi, Junpeng; Sun, Xia; Li, Jinlei; Man, Huizi; Shen, Jiangshan; Yu, Yanke; Zhang, Hongwu
Abstract: In this paper, near infrared-emitting long-persistence luminescent porous Zn1.1 Ga1.8 Ge0.1 O4 :Cr 3+, Eu 3+ @SiO2 nanoprobes have been prepared using mesoporous silica nanospheres both as morphology-controlling templates and as vessels. These nanoprobes possessed an excellent capacity for drug delivery and allowed for real-time monitoring of the delivery routes of the drug carriers in vivo . The nanoprobes demonstrated a typical mesoporous structure, a brighter NIR emission (696 nm) and a long afterglow luminescence that persisted for 15 d. Furthermore, after surface modification with folic acid (FA), a tumor-targeting group, these nanoprobes exhibited an excellent ability to target tumors with high sensitivity in vitro and in vivo . Importantly, these modified nanoprobes could accurately diagnose tumors and allow for long-term tumor monitoring via in situ and in vivo re-excitation by a red LED lamp. Furthermore, the drug release data demonstrated that the modified nanoprobes could be loaded with a large amount of doxorubicin hydrochloride (DOX) and showed sustained release behavior. Together, the results of this study indicate that these nanoprobes can accurately diagnose tumors, allow for long-term in vivo and in situ monitoring and release DOX in situ to cure tumors.